2017
DOI: 10.1159/000481170
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Changes after Full Laser Ablation of the Feeding Artery in Fetuses with Bronchopulmonary Sequestration

Abstract: Objective: To assess longitudinal intrathoracic changes after fetal laser surgery in fetuses with bronchopulmonary sequestration (BPS) with hydrops and/or hydrothorax. Study Design: The presence of intrafetal fluid effusions, the lung mass volume ratio (congenital pulmonary airway malformation volume ratio [CVR]), and the observed/expected lung-to-head circumference ratio (O/E-LHR) of both lungs were evaluated in a cohort of BPS fetuses with hydrops and/or hydrothorax treated with full laser ablation of the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…[9] In 2018, in a landmark paper, Cruz-Martinez et al reported full laser ablation of the feeding artery (FLAFA), successfully performed in 15 cases of BPS with pleural effusion/NIH. [8] They found that FLAFA causes the disappearance of all fetal effusions, regression of the sequestration, and normal pulmonary growth. In another longitudinal study in 2018, Riley et al reviewed 103 fetuses of BPS, four of that developed hydrops which were given maternal betamethasone; three fetuses underwent thoracentesis and/or thoracoamniotic shunt placement with subsequent hydrops resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] In 2018, in a landmark paper, Cruz-Martinez et al reported full laser ablation of the feeding artery (FLAFA), successfully performed in 15 cases of BPS with pleural effusion/NIH. [8] They found that FLAFA causes the disappearance of all fetal effusions, regression of the sequestration, and normal pulmonary growth. In another longitudinal study in 2018, Riley et al reviewed 103 fetuses of BPS, four of that developed hydrops which were given maternal betamethasone; three fetuses underwent thoracentesis and/or thoracoamniotic shunt placement with subsequent hydrops resolution.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive review of literature disclosed less than 80 published cases of BPS developing NIH which have survived after fetal therapy worldwide. [4,8,9] Cavaretto et al, in 2008 reviewed (in addition to their 8 cases) 31 cases of ELS with NIH published till 2008; these cases were treated with minimally invasive fetal therapy, and only 2 postnatal deaths were recorded confirming that fetal intervention in BPS with NIH positively improves the prognosis. [9] In 2018, in a landmark paper, Cruz-Martinez et al reported full laser ablation of the feeding artery (FLAFA), successfully performed in 15 cases of BPS with pleural effusion/NIH.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature identified 11 studies with original data of at least one case of BPS treated prenatally with USLC. 2,[12][13][14][15][16][17][18][19][20][21][22] Data on a total of 57 patients, including the five cases reported in the present series, were extrapolated and analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Estos cambios intrínsecos pueden ser evaluados clínicamente por ecografía Doppler del brazo proximal de la arteria intrapulmonar (figura 2). Nuestros estudios más recientes sugieren que la evaluación del Doppler intrapulmonar mejora notablemente la predicción del grado de hipoplasia pulmonar y la probabilidad de supervivencia neonatal (17) . Así, los casos con Doppler intrapulmonar patológico (flujo diastólico ausente o reverso) presentan una probabilidad de supervivencia neonatal de 30% comparada con 84% en aquellos casos con Doppler intrapulmonar normal, ausencia de herniación hepática y tamaño pulmonar mayor de 26%.…”
Section: Clasificación De Severidadunclassified